Best Exotic Marigold Hotel - Madden, John, 1949-; Parker, Ol, 1969-; Broadbent, Graham; Czernin, Peter; Dench, Judi, 1934-; Nighy, Bill, 1949-; Wilton, Penelope, 1946-; Patel, Dev, 1990-; Imrie, Celia, 1952-; Pickup, Ronald; Wilkinson, Tom, 1948-; Smith, Maggie, 1934-; et al. (Beverly Hills, California 20th Century Fox Home Entertainment, 2012)
"When seven cash-strapped seniors decide to 'outsource' their retirement to a resort in far-off India, friendship and romance blossom in the most unexpected ways."--Container.
Extras: "Behind the story: lights, colors and smiles" featurette ; "Casting legends" featurette.
Based on the novel "These foolish things" by Deborah Moggach.
Originally released as a motion picture in 2011.
Special features: "Behind the story: lights, colors and smiles" featurette ; "Casting legends" featurette.
Director of photography, Ben Davis ; editor, Chris Gill ; music by Thomas Newman.
Judi Dench, Bill Nighy, Penelope Wilton, Dev Patel, Celia Imrie, Ronald Pickup, Tom Wilkinson, Maggie Smith.
MPAA rating: PG-13 for sexual content and language.
Keywords: Moggach, Deborah -- Film adaptations; Older people -- Drama; Retirement -- Social aspects -- Drama; Hotels -- India -- Drama; British -- India -- Drama; French language materials; Bangalore (India) -- Drama; DVD-Video discs; Feature films -- United States; Feature films -- Great Britain; Feature films -- United Arab Emirates; Romance films; Fiction films; Feature films; Comedy films; Drama; Film adaptations; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Fiction films